A comprehensive review and future perspectives of simulation approaches in wire arc additive manufacturing (WAAM) - Zhonghao Chen; Lei Yuan; Zengxi Pan; Hongtao Zhu; Ninshu Ma; Donghong Ding; Huijun Li (International Journal of Extreme Manufacturing)
Wire arc additive manufacturing (WAAM) has emerged as a promising technique for producing large-scale metal components, favoured by high deposition rates, flexibility and low cost. Despite its potential, the complexity of WAAM processes, which involves intricate thermal dynamics, phase transitions, and metallurgical, mechanical, and chemical interactions, presents considerable challenges in final product qualities. Simulation technologies in WAAM have proven invaluable, providing accurate predictions in key areas such as material properties, defect identification, deposit morphology, and residual stress. These predictions play a critical role in optimising manufacturing strategies for the final product. This paper provides a comprehensive review of the simulation techniques applied in WAAM, tracing developments from 2013 to 2023. Initially, it analyses the current challenges faced by simulation methods in three main areas. Subsequently, the review explores the current modelling approaches and the applications of these simulations. Following this, the paper discusses the present state of WAAM simulation, identifying specific issues inherent to WAAM simulation itself. Finally, through a thorough review of existing literature and related analysis, the paper offers future perspectives on potential advancements in WAAM simulation strategies.